The Application of Carrageenan and Non-Alcoholic Anthocyanin Extraction of Rosa sp. on The Physic-Chemical Characteristics of Annona muricata L. Fruit Leather - Elfi Anis Saati; Sri Winarsih; Ratih Maulidha Aryani; Devi Dwi Siskawardani (Halalsphere, 2021)
Fruit leather is a healthy food with higher nutrition, but it has low plasticity. Annona muricata L. has potential as raw material due to high fibre and low pectin. Rosa sp. acts as the antioxidant and anthocyanin sources, while carrageenan as plasticity improvement. This research aimed to analyse the interaction of anthocyanin (10%; 15%; 20%) and carrageenan (0.1%; 0.2%; 0.3%) to the fruit leather physic-chemical characteristics. The research consisted of 2 main steps: (i) anthocyanin extraction from Rosa sp. used aquadest:citric acid (98:2) at 85°C for 30 mins. (ii) Application of anthocyanin on fruit leather. Randomised completed block design factorial was applied. The best fruit leather resulted by combination of anthocyanin 15% and carrageenan 0.3% with pH 3.65, water content 13.08%, antioxidant activity 87.61%, TDS 26.03°Brix, total acid titrated 4.23%, lightness (L) 41.07, redness (a+) 7.03, and yellowness (b+) 2.63.